VD_FINDINFO Décision / 2018 / 613 vom 29. Juni 2018 - VD Tribunal cantonal (2018)
JONCTION DE CAUSES, AUDITION OU INTERROGATOIRE, PRÉSENCE, REJET DE LA DEMANDE | 147 CPP (CH), 29 CPP (CH), 30 CPP (CH)